Implementasi Peran Bhineka Tunggal Ika Sebagai Pemersatu Bangsa Dan Juga Identitas Suatu Bangsa Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Indonesia is a country that is very famous for its friendly people and diverse culture. Indonesia has a motto which can no longer only be interpreted as values ​​that must be conveyed but rather its implementation. One of them is Bhineka Single Ika which is a motto which has an important role for the Indonesian people as a reference for good society in everyday life. The realization of the Indonesian nation's unity and integrity also rests on Bhinneka Tunggal Ika. This is because the nation of Indonesia requires infrastructure that can bring its diverse population together; in the absence of Bhinneka Tunggal Ika, there will probably be a great deal of strife because of this diversity. Based on research results, the values ​​that are interrelated between Bhinneka Tunggal Ika and religious moderation are togetherness, justice, mutual respect and harmony. Researchers also found several findings and discussions in this research, namely the role of Bhinneka Tunggal Ika as the unifier of the Indonesian nation and also the role of Bhineka Tunggal Ika as the identity of the Indonesian nation. From these roles, it can be concluded that the various roles contained in Ika's motto of unity in diversity as an entity to strengthen pluralism in Indonesia, especially in social life.